Is perfusion index a surrogate indicator of left ventricular contractility in neonates? A prospective study - Sohail V Seyad; Sunil Kumar Shambhu; Srinivasa Murthy Doreswamy (Wolters Kluwer Medknow Publications, 2023)
Introduction : Noninvasive blood pressure monitoring may not accurately reflect cardiac contractility in neonates due to low vascular tone. The perfusion index (PI) is a noninvasive method of assessing the strength of peripheral pulses. It is shown to have a significant correlation with the left ventricular output. This prospective study estimates the correlation between PI and cardiac contractility in neonates. Methods and Results : All hemodynamically stable neonates who were on substantial enteral feeds and not on any respiratory or inotropic support underwent measurement of PI and echocardiography examination. Various indices of left ventricular contractility were estimated, and the correlation coefficient between them and PI was determined. Fifty-six neonates were studied. The median (interquartile range [IQR]) PI was 1.5 (1.25-1.75). The median (IQR) PI in preterm neonates was 1.5 (1.2-1.8) and that in term neonates was 1.8 (1.25-2.7) (P = 0.064). PI had a correlation of 0.205 with fractional shortening (P = 0.129) and 0.13 with left ventricular ejection fraction (P = 0.821). The Spearman's correlation coefficient between PI and velocity of circumference fiber shortening was 0.009 (P = 0.945). The Spearman's correlation coefficient between PI and cardiac output was -0.115 (P = 0.400). Conclusion : The PI does not correlate with left ventricular contractility parameters in neonates.